2014
DOI: 10.1002/ejoc.201402577
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regioselective Hydrosilylation of Unsymmetric Alkynes Using a Phenylthio Directing Group

Abstract: Cobalt‐assisted hydrosilylation of acetylenes is particularly interesting in organic synthesis since alkynyl group functionalization can give way to more useful substructures. This study aims to answer the general question of how to control hydrosilylation regioselectivity with unsymmetric alkynyl groups. Cobalt‐catalyzed hydrosilylation is highly regioselective with alkyl‐phenylthio‐acetylenes affording corresponding cis‐α‐silyl‐α‐thioaryl‐substituted olefins. However, this reaction loses regioselectivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…[2] However,d espite the significant progress made,t here still remain challenges (e.g.,r egio-and stereocontrol), particularly for unsymmetrical internal alkynes in intermolecular reactions (Scheme 1). [5] In continuation of our studies on transformations of electron-rich alkynes, [6] we report herein the first general, mild, and highly selective process of this type (Scheme 1b). In contrast, the hydrosilylation of electron-rich alkynes (bearing an electron-donating group (EDG) at the triple bond) remains largely unknown.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…[2] However,d espite the significant progress made,t here still remain challenges (e.g.,r egio-and stereocontrol), particularly for unsymmetrical internal alkynes in intermolecular reactions (Scheme 1). [5] In continuation of our studies on transformations of electron-rich alkynes, [6] we report herein the first general, mild, and highly selective process of this type (Scheme 1b). In contrast, the hydrosilylation of electron-rich alkynes (bearing an electron-donating group (EDG) at the triple bond) remains largely unknown.…”
mentioning
confidence: 81%
“…[8] Theu se of other solvents did not improve the overall efficiencyand selectivity of the reaction. [5] We next examined ar ange of silanes ( Table 2). Furthermore,p reviously reported Pt and Co complexes were found to be ineffective (Table 1, entries 3a nd 4).…”
mentioning
confidence: 99%
“…
Non-oxidative,regioselective,and convergent access to densely functionalized oxazoles is realized in af unctionalgroup tolerant manner using alkynyl thioethers.S ulfur-terminated alkynes provideaccess to reactivity previously requiring strong donor-substituted alkynes such as ynamides.Sulfur does not act in an analogous donor fashion in this gold-catalyzed reaction, thus leading to complementary regioselective outcomes and addressing the limitations of using ynamides.Compared to other heteroatom-substituted alkynes,alkynyl thioethers are remarkably little explored in intermolecular late-transition-metal catalysis,d espite being readily accessed and robust. [1,2] Ynamides,i nc ontrast, are privileged substrates:i np-acid catalysis their donor nature aids metalalkyne coordination and affords highly polarized electrophiles,t hus providing the high chemo-and regioselectivity required for the discovery of efficient intermolecular reactions (Scheme 1a). [3,4] As the resulting inclusion of ad onornitrogen atom limits the utility of the products,r etaining the reactivity profile of these transformations whilst accessing more flexible and readily elaborated substitution patterns would be desirable.T he value of sulfur-substituted compounds [5] coupled with progress in C À Ca nd C-heteroatom bond formation from CÀSbonds, [6] renders alkynyl thioethers appealing alternatives to ynamides.I ndeed the ketenethionium pathway (Scheme 1a)f rom alkynyl thioethers has recently been invoked in proton-catalyzed reactions with nitriles [2g,h] and gold-catalyzed reactions with sulfides.
…”
mentioning
confidence: 99%
“…In contrast, the hydrosilylation of electron-rich alkynes (bearing an electron-donating group (EDG) at the triple bond) remains largely unknown. [5] In continuation of our studies on transformations of electron-rich alkynes, [6] we report herein the first general, mild, and highly selective process of this type (Scheme 1b). Specifically,w eh ave developed an efficient rutheniumcatalyzed intermolecular hydrosilylation of internal thioalkynes with high regio-and stereoselectivity.I nt his study, we also observed unprecedented syn addition selectivity with [Cp*Ru(MeCN) 3 ] + (Cp* = pentamethylcyclopentadienyl), awell-known catalyst for anti addition reactions of alkynes.…”
mentioning
confidence: 81%
“…Furthermore,p reviously reported Pt and Co complexes were found to be ineffective ( Table 1, entries 3a nd 4). [5] We next examined ar ange of silanes ( Table 2). Most of them gave the product either in moderate yield or with moderate selectivity;h owever,t ris(trimethylsiloxy)silane (2h)provided the product in quantitative yield with excellent selectivity ( Table 2, entry 7).…”
mentioning
confidence: 99%